2009
DOI: 10.4314/as.v8i1.44111
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis For Litter Traits In Native By Exotic Inbred Pig Crosses

Abstract: Inbred strains generated from native and exotic pigs were compared with their F 1 and F 2 backcross populations for a range of litter performance traits. Animals were intensively reared and at 81/2 months of age, the inbred genotypes from each strain were reciprocally mated to each other to generate F 1 crossbred genotypes; while gilts from each crossbred group were backcrossed to their male parents to obtain four backcross progeny groups. Results of the study showed that the litter performances were better in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
1
7
0
5
Order By: Relevance
“…The high correlation observed between litter size at birth and at weaning is expected because an increase in the number of piglet in a litter will cause an increment in the total litter weight. The correlation between the litter size and weaning weight is corroborated with the findings of Nwakwu, 2013 [9] and Nwakwu et al, 2004 [10], that there is positive and significant correlation between the liter size, weaning weight and survival rate of piglets. The negative correlation observed between litter size and average litter weight suggested that the factors that work for the increment of the litter size also cause reduction of average weight of the piglets.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The high correlation observed between litter size at birth and at weaning is expected because an increase in the number of piglet in a litter will cause an increment in the total litter weight. The correlation between the litter size and weaning weight is corroborated with the findings of Nwakwu, 2013 [9] and Nwakwu et al, 2004 [10], that there is positive and significant correlation between the liter size, weaning weight and survival rate of piglets. The negative correlation observed between litter size and average litter weight suggested that the factors that work for the increment of the litter size also cause reduction of average weight of the piglets.…”
Section: Resultssupporting
confidence: 80%
“…The results in Table 2 was similar with Adeooye et al 2010 [4] in birth weight (1.05), weaning weight (7.08), litter size at weaning (5.72), but lower in litter weaning weight (38.85 kg) while it was higher than that of Orheruata [5] in weaning weight (4.87) and lower than that of Ngere [6] which is 14.50. The litter size at birth is lower than that of Adebambo [7] and Nwakpu and Ugwu [8].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies by Nwakpu and Omeje (2004), Nwakpu and ugwu (2009) had reported positive and significant heteroses in the reciprocal crossbred but not on the main crossbred. The researcher inferred that crossing the exotic boar with native sow would yield rapid improvement especially when the parents of the crossbred are confined.…”
Section: Resultsmentioning
confidence: 99%
“…These are desirable genetic attributes that can be harnessed during crossbreeding for improvement of litter size and reproductive traits among native pig genotypes before they become extinct. Our native pigs, according to Nwakpu and Ugwu, (2009), are noted to compare favorably in growth characteristics with their exotic counterparts and have the singular ability to transmit genes for early age at sexual maturity, good maternal ability, most probable producing ability (MPPA) and produced better heterosis in harsh conditions when crossed with the exotic breed.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid efficiency is sometimes higher than the level attained by the better parent breed in a given parameter. The effect of heterosis may vary in intensity depending on the type of performance traits (Nwakpu & Ugwu 2009). The effect of cross-breeding is generally more prominent in the case of low-heritable traits, i.e.…”
Section: Introductionmentioning
confidence: 99%